2004
DOI: 10.1113/jphysiol.2004.066704
|View full text |Cite
|
Sign up to set email alerts
|

Defective respiratory amiloride‐sensitive sodium transport predisposes to pulmonary oedema and delays its resolution in mice

Abstract: Pulmonary oedema results from an imbalance between the forces driving fluid into the airspace and the biological mechanisms for its removal. In mice lacking the α-subunit of the amiloride-sensitive sodium channel (αENaC(−/−)), impaired sodium transport-mediated lung liquid clearance at birth results in neonatal death. Transgenic expression of αENaC driven by a cytomegalovirus (CMV) promoter (αENaC(−/−)Tg+) rescues the lethal pulmonary phenotype, but only partially restores respiratory sodium transport in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 37 publications
7
78
0
2
Order By: Relevance
“…The physiological importance of α-ENaC in the lung has been demonstrated in a study of α-ENaC-knockout mice, where respiratory distress and mortality were observed ≤40 h after birth, as a consequence of an inability to clear fluid from the lungs (5). Furthermore, experimental evidence has indicated that a reduction in α-ENaC expression may impair the resolution of pulmonary edema in patients with ALI (6).…”
Section: Introductionmentioning
confidence: 99%
“…The physiological importance of α-ENaC in the lung has been demonstrated in a study of α-ENaC-knockout mice, where respiratory distress and mortality were observed ≤40 h after birth, as a consequence of an inability to clear fluid from the lungs (5). Furthermore, experimental evidence has indicated that a reduction in α-ENaC expression may impair the resolution of pulmonary edema in patients with ALI (6).…”
Section: Introductionmentioning
confidence: 99%
“…Rescuing ␣ENaC (Ϫ/Ϫ) KO by ␣ENaC expression driven by the cytomegalovirus promoter leads to viable mice but with reduced ENaC expression in the kidney, colon, and lung (37,61). These mice present increased lung edema and diminished lung liquid clearance in lung injury produced by thiourea or hyperoxia (22). In humans, respiratory distress syndrome has been reported in premature babies with type 1 pseudohypoaldosteronism, a rare genetic disease where ENaC is defective (1,53).…”
mentioning
confidence: 99%
“…PQ uptake is significantly prevented when extracellular sodium is reduced (Dinis-Oliveira et al, 2006). The amiloride-sensitive cation channel is a major sodium channel, and Na + /K + -ATPase is important for its activation (Dada and Sznajder, 2003;Eaton et al, 2004;Egli et al, 2004;Folkesson and Matthay, 2006;Kemp and Kim, 2004;Planès, et al, 2005;Matalon et al, 2002), as are potassium channels (O'Grady and Lee, 2003). The gene expression alterations of the Na + /Cl − -dependent neurotransmitter transporter gene, Slc17a1, Kcne1, Kcna1, Kcna4, Scn4a, Scn2b, Atp1a2, Accn2, and Accn3 could indicate changes in these functions.…”
Section: Discussionmentioning
confidence: 99%